Promoting Inter-Asian understanding through English: Cross-border exchanges through an Asian Youth Program - Kip Cates (Universitas Katolik Indonesia Atma Jaya, 2017)
This paper discusses the importance of going beyond the classroom to provide EFL learners with out-of-class opportunities to use their language skills in real-world situations with same-age peers. It introduces the Asian Youth Forum (AYF), a unique series of international youth conferences designed by English language educators in Asia that aims at promoting cross-cultural awareness, communication skills, leadership and international understanding through the medium of English-as-a-global-language. The Asian Youth Forum is an annual 1-week event that brings together college-aged EFL students from across the Asian region. Participants typically comprise 30 - 80 young people from 10 - 15 countries such as Japan, Korea, Thailand, Indonesia, Vietnam, Cambodia and the Philippines. During this all-English event, students take part in a rich program of academic seminars, presentations and social events built around the themes of language, culture, global issues, and leadership. This paper outlines the aims and history of the Asian Youth Forum, describes its design and special features and reports on the program's outcomes in terms of student attitudes, language development, learner identity and international understanding. The author concludes by calling for further EFL youth exchanges of this type in other regions of the world.